Communications - Stability of Inclusions and the Formation of Secondary Grains in Silicon-Iron Alloys - M. Markuszewicz; J. Groyecki; J. Lassota; A. Zawada (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1967)
The ratio of stable to unstable inclusions was found to ploy an essential role in the process of sccorldar-y recrystatlizalion in Si-Fe. The analysis of the free energy of inclusions in the range of heat-treatment of individual inclusions to be predicted. The effects MnS. ns inslable inclusions. were investigated. TO secure a high induction, the secondary recryslulliztt-lion associated wilh the texture is necessary. To obtain a low core loss an additional refiuing in the solid state is required. It has been found that sulfur can be more easily removed in racunm than in hydrogen and thai this process was hindered by the prescrzce of INCLUSIONS play an essential role in the development of cube-on-edge texture in Si-Fe. Their function consists in restraining the growth of primary grains up to about 900°C and in passing subsequently into solution at higher temperatures. This process is accompanied by the selective growth of secondary grains with (110)[001] orientation. The general effect of inclusions depends on such factors as the type of impurities, their amount. dispersion and stability, the conditions of diffusion in the space of lattice of metal, and the reactions at the metal/gas interface. In recent years, some of these factors were the subject of a special investigation. A positive influence of Mns, siN,' and vN3 has been established. The quantity of impurities4 and their dispersion5 have been found to be of major importance. Attention was called to the vital importance of diffusion and the conditions under which the impurities are removed from metal., It has also been demonstrated that in Fe-Si alloys by the techniques of powder metallurgy a special opportunity exists to obtain the (110)[001] type texture. 6 The aim of this work was to conduct qualitative investigations on the influence of inclusion stability on the development of cube-on-edge texture in a metal containing approximately 3 pct Si. Experiments were carried out on cast alloys and on those manufactured by powder-metallurgy techniques. The results obtained from these experiments were utilized to explain the phenomena involved and to analyze the relationships between stable and unstable inclusions and the magnetic properties of alloys. EXPERIMENTS AND RESULTS The raw materials used in these experiments were the powder of carbonyl iron with the analysis (in pct) 0.044 C, 0.01 Mn, 0.005 Si, 0.009 P, 0.002 S, traces of Cu, 0.06 Ni, 0.0015 Al, 0.03 Cr, 0.02 Mo, 0.01 Ti, 0.002 Co, traces of Pb, and the powder of silicon containing 94.14 Si, 0.003 S, 0.048 C. The powders were ground and mechanically mixed in 100-g batches. and then pressed at 9 tons per sq cm into 74 by 24 by 8 mm blocks. Sintering was carried out at 1100°C for 12 hr in vacuum (2 x lo-' Tr) or in hydrogen. In this instance the material was heated slowly and subjected to prolonged soaking at 350°, 650°, and 750 2C, respectively, to secure reduction of ferro-oxides. This was checked by making measurements of the dew point, which was found to change from -15" to -35°C after reduction. The compacts after sintering were hot-rolled to 2.4 mm, annealed at 800 C, and finally cold-reduced to 0.35 mm with intermediate annealing at 800°C at a gage of about 0.8 mm. Impurities were added in the powdered form and mixed with iron and silicon powders. Sulfur in the elemental state, electrolytic manganese, and pure aluminum oxide were employed. Besides, to obtain a material with low contents of impurities, especially